Global sociology : introducing five contemporary societies - Schneider, Linda; Silverman, Arnold R. , 1940- (McGraw-Hill, 2013)
"An effective supplement to any standard sociology text, this broad and comprehensive sociological description of five diverse contemporary societies with wide geographic distribution - Japan, Mexico, Egypt, Germany and the San peoples of Namibia - is organized around basic sociological topics: culture, social structure, group life, socialization, deviance, social institutions, social stratification, and social change. Fictional vignettes of individuals in each country help students experience first-person viewpoints on life in five very different societies. By comparing other societies with their own, students read about the range of social variation, learn what makes their own society distinctive, and gain a unique and fascinating vantage point on what sociology offers in a world of rapid social change."--pub. desc.